CGRP and migraine: from bench to bedside - Edvinsson, L. (Revue neurologique, 2021)
Migraine treatment has reached a new era with the development of drugs that target the trigeminal neuropeptide calcitonin gene-related peptide (CGRP) or its receptor. The CGRP related therapies offer considerable improvements over existing drugs as they are the first to be designed to act on the trigeminal pain system, more specific and with few adverse events. Small molecule CGRP receptor antagonists, such as rimegepant and ubrogepant, are effective for the acute treatment of migraine headache. In contrast, monoclonal antibodies against CGRP or the CGRP receptor are beneficial for the prophylactic treatments in chronic migraine. Here I will provide a historical overview of the long path that led to their successful development. In addition, I will discuss aspects on the biology of CGRP signalling, the role of CGRP in migraine headache, the efficacy of CGRP targeted treatment, and synthesize what currently is known about the role of CGRP in the trigeminovascular system.